KEPENTINGAN INDONESIA MENYEPAKATI COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT DENGAN UNI EROPA TAHUN 2011-2016 - Alfajri "; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describe the interest of Indonesia dealed about comprehensive economic partnership agreement with European Union in 2011-2016. European Union are one of most countries in the world that have big potency for investations and Indonesia have been export some product to European Union. In order that export product from Indonesia always get protctionism and restriction for European Union regulations.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the interest of Indonesia dealed about comprehensive economic partnership agreement with European Union. The theories applied in this research are liberalis with the foreign policy theory from KJ Holsti.The result shows that the interest of Indonesia dealed about comprehensive economic partnership agreement with European Union are becaused the protections and restriction regulation from Eurpoean Unions likes tariff and non tariff policy for product from Indonesia, standarization product from European Union and minims of infrastructure from Indonesias product.Key words: interest, protections, partnership and aggrement